Cytotoxic Constituents from Podocarpus fasciculus - Liao, Chia-Ching; Liang, Yu-Han; Hwang, Shy-Yuan; Wu, Ming-Der; Kuo, Yao-Haur; Ho, Hsiu-O; Kuo, Yu-Jen (Chemical & Pharmaceutical Bulletin, 2008)
A new diterpene, 16-hydroxy communic acid (1), along with thirty one known compounds including five norditerpenes (2—6), twenty two flavonoids containing four biflavonoids (7—10), nine monoflavonoids (11—19) and nine flavanoid glycosides (20—28), as well as four phenolic constituents (29—32) were isolated from the 95% ethanolic extract of Podocarpus fasciculus. The structure of 1 was elucidated using spectral methods. Of these isolates, nagilactone C (2) showed the most significant inhibitory effects against DLD cells (human colon carcinoma) (ED50=2.57 μg/ml) and compounds 7, 8, 10, 11, and 12 had moderate cytotoxic activity against human KB (human oral epithelium carcinoma), Hela (human cervical carcinoma), Hepa (human hepatoma), DLD (colon carcinoma), and A-549 (human lung carcinoma) tumor cell lines. Preliminary structure–activity relationship studies of the isolated diterpenoids and biflavonoids are discussed.